Detection and identification of species-specific bacteria associated with synanthropic mites - Hubert, Jan; Kopecký, Jan; Perotti, M Alejandra; Nesvorná, Marta; Braig, Henk R; Ságová-Marečková, Markéta; Macovei, Lilia; Zurek, Ludek (Microbial ecology, 2012)
Internal bacterial communities of synanthropic mites Acarus siro, Dermatophagoides farinae, Lepidoglyphus destructor, and Tyrophagus putrescentiae (Acari: Astigmata) were analyzed by culturing and culture-independent approaches from specimens obtained from laboratory colonies. Homogenates of surface-sterilized mites were used for cultivation on non-selective agar and DNA extraction. Isolated bacteria were identified by sequencing of the 16S rRNA gene. PCR amplified 16S rRNA genes were analyzed by terminal restriction fragment length polymorphism analysis (T-RFLP) and cloning sequencing. Fluorescence in situ hybridization using universal bacterial probes was used for direct bacterial localization. T-RFLP analysis of 16S rRNA gene revealed distinct species-specific bacterial communities. The results were further confirmed by cloning and sequencing (284 clones). L. destructor and D. farinae showed more diverse communities then A. siro and T. putrescentiae. In the cultivated part of the community, the mean CFUs from four mite species ranged from 5.2 × 10(2) to 1.4 × 10(3) per mite. D. farinae had significantly higher CFUs than the other species. Bacteria were located in the digestive and reproductive tract, parenchymatical tissue, and in bacteriocytes. Among the clones, Bartonella-like bacteria occurring in A. siro and T. putresecentiae represented a distinct group related to Bartonellaceae and to Bartonella-like symbionts of ants. The clones of high similarity to Xenorhabdus cabanillasii were found in L. destructor and D. farinae, and one clone related to Photorhabdus temperata in A. siro. Members of Sphingobacteriales cloned from D. farinae and A. siro clustered with the sequences of "Candidatus Cardinium hertigii" and as a separate novel cluster.
Keywords: Animals; Mites; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Acari; Bacteria; polymorfismus délky restrikčních fragmentů; Molecular Sequence Data; polymerázová řetězová reakce; sekvenční analýza DNA; RNA ribozomální 16S; Cloning, Molecular; roztoči; Dermatophagoides farinae; zvířata; Species Specificity; Polymorphism, Restriction Fragment Length; Polymerase Chain Reaction; hybridizace in situ fluorescenční; klonování DNA; In Situ Hybridization, Fluorescence; druhová specificita; molekulární sekvence - údaje